Strategy For Developing Maharah Al-Kalam Through the Use of Social Media - Khusni, Achmad Robith; Muzammil, Ahmad ((الطموحات ) EL-THUMUHAT, 2026)
Abstract The development of digital technology and the high use of social media among students demands innovation in Arabic language learning, especially in maharah al-kalam. This study aims to describe strategies for developing maharah al-kalam through the use of social media. This study uses a descriptive qualitative approach with a literature review method. The results show that social media such as Instagram, YouTube, and TikTok are effective in supporting speaking learning because they are flexible, interactive, and contextual. The strategies applied include modelling, shadowing technique, content-based speaking, and project-based speaking, which have been proven to improve students' fluency, vocabulary mastery, and confidence. With proper planning and supervision, social media has the potential to be an effective medium for learning maharah al-kalam in the digital age. Keywords: maharah al-kalam; social media; Arabic language